Pengaruh Tunjangan Sertifikasi, Motivasi Dan Keahlian Terhadap Kinerja Guru Di SMK GKPS 2 Pematangsiantar - Jon Efenri Saragih; Hisarma Saragih; Ika Rosenta Purba (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Efforts to improve the quality of education through improving the quality of teachers, in maximizing teacher performance, the Government provides teachers with basic living needs. Because teacher performance can improve the quality of education. The purpose of this research is to analyze Certification Allowances, Motivation and Skills on Teacher Performance at SMK GKPS 2 Pematangsiantar. This research was carried out at SMK GKPS 2 Pematangsiantar. The population of this research were all 43 teachers at SMK GKPS 2 Pematangsiantar. The total population is used as a sample. Data collection was carried out by collecting premier data through a questionnaire, the questionnaire was created based on indicators of Certification Allowances, Motivation, Skills and Teacher Performance. The analysis method uses multiple linear regression analysis by testing Simultaneous and Partial Hypotheses. The results of this research show that the Certification Allowance has a positive and significant effect on the performance of Teachers at SMK GKPS 2 Pematangsiantar. Motivation has a positive and significant effect on the performance of teachers at SMK GKPS 2 Pematangsiantar. Expertise has a positive and significant effect on the performance of teachers at SMK GKPS 2 Pematangsiantar. Certification allowances, motivation and expertise simultaneously have a positive and significant effect on teachers at SMK GKPS 2 Pematangsiantar. The existence of Certification Allowances can improve the quality of education, increase teacher motivation. Leaders provide support and encouragement to teachers. Increase teacher expertise by actively participating in training and recruiting teachers according to existing expertise at SMK GKPS 2. Teacher performance can increase if teacher needs are met, there is motivation. leadership and supported by the expertise of teachers.